191 Atheroprone Flow Alters ATP-Induced Calcium Signalling in the Endothelium. (3rd June 2016) - Green, Jack; Evans, Paul; Wilson, Heather
Abstract : Introduction: The development of the atherosclerotic plaque occurs at distinct points in the vasculature, with areas such as bends and branch points susceptible to plaque formation. The endothelium at these sites is influenced by a disturbed blood flow with low wall shear stress. Numerous studies have shown that stimulation of endothelial cells with this flow pattern induces several inflammatory signalling pathways, but the mechanisms in which this flow pattern is sensed remain unclear. ATP is released extracellularly from endothelial cells in response to shear stress. The endothelium expresses the ATP-gated cation channels P2X4 and P2X7, which have been previously shown to respond to shear stress induced ATP release. Their expression is also increased in the endothelium following inflammatory stimulation. Therefore, we hypothesise that P2X receptors are involved in sensing atheroprone flow and inducing inflammatory signalling, thereby promoting development of atherosclerosis. Methods: Human Umbilical Vein Endothelial Cells (HUVECs) were cultured under flow for 72 h using an ibidi flow pump system. Atheroprotective flow was applied using +13 dyn/cm 2 and ± 4 dyn/cm 2 (0.5hz) was used for atheroprone flow. After flow conditioning, HUVECs were then loaded with a fluorescent calcium dye (CAL-520) and their response to 300Î¼M BzATP was measured. Results: Endothelial cells preconditioned with atheroprone flow showed an enhanced calcium response after BzATP stimulation. This enhancement was dependent on extracellular calcium as no increase was detected when performed in calcium free extracellular buffer. The expression level of P2X4 and P2X7 receptors was significantly enhanced in HUVECs preconditioned with atheroprone flow compared to atheroprotective. Moreover the expression of the cell surface ATPase CD39, which breaks down extracellular ATP, was increased under atheroprotective flow. Chemical inhibition of CD39 with ARL-67156 also significantly enhanced the calcium response to BzATP in cells under atheroprotective, but not atheroprone flow. Conclusions: We have identified an enhanced ATP induced calcium response and expression of the ATP-gated P2X4/7 receptors in HUVEC under atheroprone flow conditions. We observed enhanced expression of the cell surface ATPase CD39 in endothelial cells under atheroprotective flow suggesting that extracellular ATP is more rapidly hydrolysed to adenosine under such conditions. We therefore propose that shear stress induced ATP plays a role in specifically activating cells under atheroprone flow and induces inflammatory signalling pathways, underlying atherogenesis susceptibility in vulnerable regions of the vasculature.